Design of a novel family of bifunctional phase-transfer catalysts and their applications in the kinetic resolution of 2-oxindole derivatives - Sorrentino, Emiliano (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
The design and synthesis of a biomimetic organocatalyst mimicking the active site of aspartate proteases have been undertaken. The design was aimed at constructing an artificial enzyme bearing two carboxylic acid groups at a distance approximately identical to that present between the two aspartate residues encountered in the active site of aspartate proteases involved in the catalytic protein cleavage. A new synthetic pathway was devised which led to the synthesis of two novel compounds in good yields. Both of these novel derivatives had the potential to behave as aspartate protease biomimetic species, however they presented significant drawbacks. One was poorly soluble in aqueous solutions (the solvent normally involved in enzyme-mediated biochemical transformations) while the other, when evaluated as a biomimetic catalyst for the cleavage of the more labile ester bond (compared to the amide bond), did not seem to bring about any enhancement of the hydrolysis rate for the ester under investigation.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.